Financial Inclusion through Digital Services: A Bibliometric Analysis of Global Banking Perspectives - Judijanto, Loso (The Es Accounting And Finance, 2025)
This study conducts a bibliometric analysis to examine the evolution and intellectual structure of research on financial inclusion through digital services within the global banking sector. Utilizing data sourced exclusively from Scopus and analyzed through VOSviewer, the study maps the thematic landscapes and collaboration networks in the literature from 2000 to 2024. Key findings indicate a strong emphasis on technological innovations such as mobile banking, digital payments, and blockchain, which are central to discussions on enhancing financial access. The research highlights significant contributions from diverse geographical regions, with a notable predominance of work from China and the United States. Temporal trends reveal an increasing integration of financial inclusion initiatives with broader economic and sustainable development goals. The study underscores the transformative potential of digital financial services and suggests strategic directions for future research. Limitations include the focus on English-language publications and the quantitative nature of bibliometric analysis. This research contributes to the understanding of how digital innovations are reshaping financial inclusion, offering insights that can guide policy and practice in creating more inclusive financial systems.